2012
DOI: 10.3346/jkms.2012.27.8.929
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Complex Regional Pain Syndrome and Working Life: A Korean Study

Abstract: Complex regional pain syndrome affects the quality of life of the patient. The aim of this study was to investigate the epidemiological features of this syndrome and evaluate its effect on the patient's working life. We demonstrated that the disease has a male preponderance and is 3 times more likely to affect the lower extremities. In this study, 11 participants (20%) retained their employment, whereas 44 (80%) became unemployed. Mean age and pain score were lower in the employment group than in the unemploym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 19 publications
5
12
0
Order By: Relevance
“…Although some studies have found that CRPS often occurs in the upper limb, 3 9 10 18 20 other studies have shown cases of symptoms in the lower limbs. 16 17 19 The present study is consistent with these previous works, as 11 of the 23 cases involved CRPS occurring in the lower limbs and nine in the upper limbs. Further, this study found that the average period from disputed medical procedure to diagnosis was one year and two months.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Although some studies have found that CRPS often occurs in the upper limb, 3 9 10 18 20 other studies have shown cases of symptoms in the lower limbs. 16 17 19 The present study is consistent with these previous works, as 11 of the 23 cases involved CRPS occurring in the lower limbs and nine in the upper limbs. Further, this study found that the average period from disputed medical procedure to diagnosis was one year and two months.…”
Section: Discussionsupporting
confidence: 93%
“…This result is similar to those of previous studies in Korea, which found that the ratio of CRPS types I to II was 7:3, 16 and 92.7% of all subjects had CRPS type I. 17 …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…[1214] One possible explanation for this finding could be that obligatory military service in Korea may have increased the risk of trauma and CRPS in young males. Indeed, a previous epidemiologic study of the Korean population [15,16] showed similar characteristics to our study population.…”
Section: Discussionsupporting
confidence: 86%